Sport aggression in relation to alcohol consumption amongst athletes - Chia, Perlina Jiaqi (2019)
Background: The consumption of alcohol has increased by 0.6 litres per-capital between 1990 and 2017 (Manthey et al., 2019). Increased alcohol consumption puts these individuals at greater risk of aggressive behaviour and substance abuse (O’Brien et al., 2018). Little study has addressed the relationship between alcohol use and aggression behaviours of athletes in local setting. As such, the objective of this study is to understand the aggression levels of athletes in Singapore and its relationship with alcohol. Methods: A quantitative study design via self-reported questionnaire was implemented for this study. Participants were recruited via word of mouth, personal connections, and advertisements using social media. Singaporeans aged 21 years and above, had no diagnosed medical conditions, and were current students in Singapore were eligible for the study. Microsoft Excel and Jamovi was used to analyse the data received. Results: A total of 306 responses collected from an online survey. Athletes had higher means for all trait aggression as compared to non-athletes, especially for physical aggression where p=0.045. The no alcohol group were more aggressive than the alcohol group. Besides addressing our hypothesis, this study found that male participants were more likely to binge drink, and females were more aggressive than males. Discussion: Student athletes in Singapore demonstrated more aggressive traits when under the influence of alcohol, as compared to non-athlete students. Our study was not able to provide conclusive data between alcohol and no alcohol group due to the wide difference in sample size. Gender differences in alcohol use and aggression was noted in our study.